Analysis of the Effect of 3D Printing Process Parameters on the Testing of Polylactic Acid (PLA) Specimens - Ahmad Ridho; Firman Alhaffis (International Journal of Science and Environment (IJSE), 2026)
3D printing technology using the Fused Deposition Modeling (FDM) method has been widely adopted in manufacturing processes due to its ability to produce complex-shaped products at relatively low cost and with high production efficiency. However, the mechanical properties of printed products are significantly influenced by printing process parameters. This study aimed to analyze the effects of infill density, printing speed, and printing orientation on the mechanical properties of Polylactic Acid (PLA) specimens and to determine the optimal parameter combination using the Taguchi method. An experimental approach was employed using a Creality K1 3D printer and PLA filament. Tensile test specimens were manufactured according to the ASTM D638 standard, while compression test specimens were prepared based on the ASTM D695 standard. The experimental data were analyzed using the Taguchi method through the Signal-to-Noise (S/N) ratio to evaluate the influence of each process parameter and identify the optimal parameter combination. The results indicated that variations in the 3D printing process parameters significantly affected the mechanical properties of PLA specimens under both tensile and compression testing. Based on the Taguchi analysis, the optimal parameter combination consisted of an infill density of 0.1, a printing speed of 100 mm/s, and a horizontal printing orientation, which produced the best mechanical performance. Furthermore, the S/N ratio analysis revealed that printing orientation was the most influential parameter affecting the mechanical properties, followed by infill density, while printing speed had the least influence. Therefore, the Taguchi method proved to be an effective approach for determining the optimal process parameter combination to improve the mechanical quality of PLA specimens produced using the FDM 3D printing process.